An Electronic Economic Controller for automatically adjusting the intensity of Solar-Powered LED Street Lightning Systems in rural areas (GUB Journal of Science and Engineering, 2024)
Using photovoltaic energy for street lighting systems is increasing rapidly in rural areas. An economic and smart controller design for automatic intensity control of LED-based street lights is the main challenge. In this work, an electronic-based controller is proposed for controlling the LED light intensity automatically, considering vehicle movement and atmospheric conditions. A HC-SR501 PIR sensor is used for detection of vehicle movements and to assist the controller in making decisions regarding the brightness of the LED. The proposed LED is operated at three different energy levels, such as 0 W, 10 W, and 30 W. In the daytime, the load will remain off, and at night, the LED will operate at two power levels, 33% and 100%, based on the vehicle occupancy rate. In addition, the proposed controller will enhance the battery lifetime. Furthermore, the proposed work ensures significant savings in energy and operating costs and also favors environmental responsibility. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 9(1), 2022 P 58-65